The The Effect of The Problem Based Learning Model Integrated with Culturally Responsive Teaching on The Numeracy Skills and Mathematical Dispositions - Ja'faruddin Ja'faruddin; Resky Fadila Amin; Awi Dassa (Proximal: Jurnal Penelitian Matematika dan Pendidikan Matematika, 2025)
This study analyzes the effectiveness of implementing Culturally Responsive Teaching (CRT) within a Problem Based Learning (PBL) framework in mathematics instruction at SMP Negeri 2 Takalar and examines its impact on students’ numeracy skills and mathematical dispositions. This research employed a pre-experimental one-group pretest–posttest design involving 28 eighth-grade students, using numeracy tests, classroom observations, student response questionnaires, and mathematical disposition scales as instruments. The findings show that CRT was implemented effectively through the integration of local cultural contexts, inclusive interactions, and active student participation. Students’ numeracy skills improved significantly, with posttest scores surpassing the Minimum Mastery Criteria (KKM) and N-Gain values falling within the medium to high categories. Student activity levels were categorized as active, responses were positive, and mathematical dispositions increased to the medium category. These results indicate that the application of CRT contributes to enhancing students’ numeracy skills and supports mathematics learning that is more meaningful, contextual, and culturally grounded.